(untitled) ("Conference on Universal Science Research 2023", 2025)
Pediatric stroke represents a rare but severe neurological condition associated with significant morbidity and long-term disability. In arid regions, extreme climatic factors such as chronic dehydration, high ambient temperatures, and environmental stressors may contribute to unique pathophysiological mechanisms influencing the onset and clinical course of cerebrovascular events in children